2015
DOI: 10.1155/2015/502105
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Are Required for Human Mesenchymal Stem Cells to Initiate Proliferation after the Quiescence Exit

Abstract: The present study focuses on the involvement of reactive oxygen species (ROS) in the process of mesenchymal stem cells “waking up” and entering the cell cycle after the quiescence. Using human endometrial mesenchymal stem cells (eMSCs), we showed that intracellular basal ROS level is positively correlated with the proliferative status of the cell cultures. Our experiments with the eMSCs synchronized in the G0 phase of the cell cycle revealed a transient increase in the ROS level upon the quiescence exit after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…We thus measured the ROS levels in GARP −/low ASCs and detected a significant increase in the levels of mtROS compared with control cells. Although physiological levels of ROS in MSCs are necessary for their proliferation and adipogenic/chondrogenic differentiation capacity, high endogenous ROS levels can have detrimental effects on MSCs, including the induction of DNA damage and premature senescence, impairment of MSC migration, and a reduction in their immunomodulatory and osteogenic capacities . We found that reducing the levels of mtROS in GARP −/low ASCs using the mitochondria‐targeted antioxidant mitoTEMPO, decreased the amount of DSBs, and partially reversed their block in proliferation.…”
Section: Discussionmentioning
confidence: 74%
“…We thus measured the ROS levels in GARP −/low ASCs and detected a significant increase in the levels of mtROS compared with control cells. Although physiological levels of ROS in MSCs are necessary for their proliferation and adipogenic/chondrogenic differentiation capacity, high endogenous ROS levels can have detrimental effects on MSCs, including the induction of DNA damage and premature senescence, impairment of MSC migration, and a reduction in their immunomodulatory and osteogenic capacities . We found that reducing the levels of mtROS in GARP −/low ASCs using the mitochondria‐targeted antioxidant mitoTEMPO, decreased the amount of DSBs, and partially reversed their block in proliferation.…”
Section: Discussionmentioning
confidence: 74%
“…A recent study conducted by Lyublinskaya and colleagues found that reactive oxygen species (ROS) are required for MSC to initiate proliferation [31]. Additionally, reduced level of basal oxidative phosphorylation will lead to a reduced ROS in MSC [21,32].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity has been shown to decrease in response to ROS [47] . Furthermore, the addition of ROS to bone marrow-derived stromal cells or osteoblastic precursors inhibited the expression of different osteogenic markers in a dose dependent manner [34] , [48] . Thus, there is an inverse correlation between the level of ROS and bone differentiation.…”
Section: Reactive Oxygen Species and Stem Cell Differentiationmentioning
confidence: 98%
“…With the basal level of ROS, MSCs would remain quiescent. The ROS level would increase before the cells enter the S phase of the cell cycle, and antioxidants block the G 1 -S transition [34] . Urao et al, in 2008, found that deletion of Nox2 causes reduced stem cell mobilization from the bone marrow to peripheral blood [35] .…”
Section: Reactive Oxygen Species and Keeping The Stem Cell Potencymentioning
confidence: 99%